Synthesis of cation substituted LiMn2-xMxO4 (M=A1,Ni) cathode materials for a lithium ion battery: improving energy storage, capacity retention, and lithium transport - Kunjuzwa, Nikiwe (My University, 2017)
Spinel LiMn2O4 cathode materials continues attracting the attention of researchers globally due to its economic, environmental and electrochemical benefits it provides in the lithium ion battery field. Obviously, it also experiences drawbacks in terms of its poor cycle life due to severe capacity fading. In this study, the necessary effort to improve the capacity retention, the Li+ ion diffusion and increasing the energy density by increasing the voltage of the spinel LiMn2O4 cathode materials. We have used small amounts of aluminium and then with nickel, and succeeded in following an effective doping method which uses wet chemistry synthesis techniques namely solution combustion, and aqueous reduction methods. We further explored the utilization of the South African manganese precursor, electrolytic manganese dioxide (EMD from a South African supplier). In chapter 3, we were able to enhance the capacity retention of LiMn2O4 by aluminium doping. We have synthesized LiAlxMn2-xO4 (x = 0, 0.125, 0.25, 0.375, and 0.5) cathode materials for Li ion batteries using metal nitrates and urea as precursors by a solution-combustion method. The first cycle discharge capacity of LiAl0.125Mn1.875O4 is comparable to that of the pristine LiMn2O4, just as the values of their lattice parameter are essentially the same. In addition, the LiAl0.375Mn1.625O4 sample exhibited a more stable discharge capacity than the other samples. The variation in lattice parameter as a result of Al doping correlated with the greatly enhanced cyclability of the discharge capacity of the LiMn2O4 spinel. In chapter 4, we studied the electrochemical performance of LiNixMn2-xO4 (x=0, 0.1, 0.2) spinel cathode material synthesized by solution combustion method. The nickel substituted samples exhibited excellent capacity retention (> 99%) and the use of a low amount of Ni adopted to eliminate the Jahn-Teller effects of the LMO; and enhanced lithium ion transport compared to the LMO. Based on the promising results achieved in this work we have decided to attempt to get similar results by employing the South African manganese resource, electrolytic manganese dioxide (EMD), rather than using manganese nitrate from Sigma Aldrich. In chapter 5, we employed electrolytic manganese dioxide (EMD) as manganese precursor and a low temperature aqueous reduction synthesis technique to successfully prepare a low content nickel substituted spinel LiNixMn2-xO4 cathode for a lithium ion battery by using NiSO4·6H2O as nickel source. All nickel substituted samples LiNixMn2-xO4 (x = 0.05, 0.1, 0.2) exhibited superior capacity retention as compared to pristine LiMn2O4. In chapter 6, we successfully synthesized nickel substituted spinel LiMn2-xNixO4 cathode materials for lithium ion battery by using Ni(NO3)2.6H2O as nickel source using electrolytic manganese dioxide (EMD). All nickel substituted samples LiMn2-xNixO4 (x = 0.05, 0.1, 0.2) exhibited superior capacity retention when compared to pristine LiMn2O4. The results confirmed that a Ni(NO3)2·6H2O nickel source performed electrochemically better than a NiSO4·6H2O nickel source. In chapter 7, we examined the impedance and Li+ ion diffusion properties of as-synthesized nickel substituted LiNixMn2-xO4 cathodes from two kinds of nickel sources. The nickel nitrate source gives more suppressed impedance as compared with nickel sulfate.
A thesis submitted in fulfillment of the requirements for the degree Doctor of Philosophy in the Faculty of Science Department of Chemistry at the University of the Witwatersrand Republic of South Africa May 2017
Keywords: Nanotechnology; Lithium compound; Cations--Synthesis